Genetic diversity and population structure of wild/weedy eggplant (Solanum insanum, Solanaceae) in southern India: Implications for conservation2. Issue 1 (1st January 2015) - Mutegi, Evans; Snow, Allison A.; Rajkumar, Muthu; Pasquet, Remy; Ponniah, Hopeland; Daunay, Marie‐Christine; Davidar, Priya
Abstract : Premise of the study: Crop wild relatives represent important genetic resources for crop improvement and the preservation of native biodiversity. Eggplant ( Solanum melongena ), known as brinjal in India, ranks high among crops whose wild gene pools are underrepresented in ex situ collections and warrant urgent conservation. Knowledge of outcrossing rates and patterns of genetic variation among wild populations can aid in designing strategies for both in situ and ex situ preservation. Methods: We used 14 microsatellite (simple sequence repeat) markers to examine genetic diversity, population structure, and outcrossing in 10 natural populations of wild/weedy eggplant ( S. insanum = S. melongena var. insanum ) and three cultivated populations in southern India. Key results: Multilocus F ST analyses revealed strong differentiation among populations and significant isolation by distance. Bayesian model‐based clustering, principal coordinate analysis, and hierarchical cluster analysis grouped the wild/weedy populations into three major clusters, largely according to their geographic origin. The three crop populations were similar to each other and grouped with two wild/weedy populations that occurred nearby. Outcrossing rates among the wild/weedy populations ranged from 5–33%, indicating a variable mixed‐mating system. Conclusion: Geographic isolation has played a significant role in shaping the contemporary patterns of genetic differentiation among these populations, many of which represent excellent candidates for in situ conservation. In two cases, close genetic affinity between cultivars and nearby wild/weedy populations suggests that gene flow has occurred between them. To our knowledge, this is the first study investigating population‐level patterns of genetic diversity in wild relatives of eggplant.